Identification of an Extradiol Dioxygenase Involved in Tetralin Biodegradation: Gene Sequence Analysis and Purification and Characterization of the Gene Product - Andújar, Eloísa (American Society for Microbiology, 2000)
A genomic region involved in tetralin biodegradation was recently identified in Sphingomonas strain TFA. We have cloned and sequenced from this region a gene designated thnC, which codes for an extradiol dioxygenase required for tetralin utilization. Comparison to similar sequences allowed us to define a subfamily of 1,2-dihydroxynaphthalene extradiol dioxygenases, which comprises two clearly different groups, and to show that ThnC clusters within group 2 of this subfamily. 1,2-Dihydroxy-5,6,7,8-tetrahydronaphthalene was found to be the metabolite accumulated by a thnC insertion mutant. The ring cleavage product of this metabolite exhibited behavior typical of a hydroxymuconic semialdehyde toward pH-dependent changes and derivatization with ammonium to give a quinoline derivative. The gene product has been purified, and its biochemical properties have been studied. The enzyme is a decamer which requires Fe(II) for activity and shows high activity toward its substrate (V(max), 40.5 U mg(−1); K(m), 18.6 μM). The enzyme shows even higher activity with 1,2-dihydroxynaphthalene and also significant activity toward 1,2-dihydroxybiphenyl or methylated catechols. The broad substrate specificity of ThnC is consistent with that exhibited by other extradiol dioxygenases of the same group within the subfamily of 1,2-dihydroxynaphthalene dioxygenases.